THE SENSORY PROPERTIES AND FLAVOR CHARACTERISTICS OF MEAT OF CATTLE AND BUFFALO FED PROTECTED LEMURU FISH (Bali sardinella) OIL AS DRIED CARBOXYLATE SALT MIXTURE (DCM) IN RATION - Yurleni, -; Amri, Ulil; Mardalena, -; Afdal, M. (Proceeding Buffalo International Conference, 2013)
The aim of the study was to reveal the sensory and characteristic differences between cattle and buffalo meats. There were 6 swamp buffalo and 8 Ongole cross cattle used in the study which arranged as a factorial experiment 2x2, based on a completely randomized design: 2 species and 2 level of DCM (dried carboxilated salt mixture; 0 and 45 g per kg ration). The result indicated that DCM in ration was significantly (P<0.05) strengthen the odor of the meat compared with control meat. Buffalo meat was significantly (P<0.05) darker than of cattle.